2017
DOI: 10.1074/jbc.m116.764522
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TRAF3IP2 by Genetic and Interventional Approaches Inhibits Ischemia/Reperfusion-induced Myocardial Injury and Adverse Remodeling

Abstract: Edited by Dennis R. VoelkerRe-establishing blood supply is the primary goal for reducing myocardial injury in subjects with ischemic heart disease. Paradoxically, reperfusion results in nitroxidative stress and a marked inflammatory response in the heart. TRAF3IP2 (TRAF3 Interacting Protein 2; previously known as CIKS or Act1) is an oxidative stress-responsive cytoplasmic adapter molecule that is an upstream regulator of both IB kinase (IKK) and c-Jun N-terminal kinase (JNK), and an important mediator of autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…TRAF3IP2 (TRAF3 interacting protein 2; previously known as CIKS or Act1) is an oxidative stress-responsive cytoplasmic adapter molecule that is an upstream regulator of both IκB kinase (IKK) and JNK. Ischemia/reperfusion up-regulates TRAF3IP2 expression in the heart, and its gene deletion, in a conditional cardiomyocyte-specific manner, significantly attenuates ischemia/reperfusion-induced oxidative stress, IKK/NF-κB and JNK/AP-1 activation, inflammatory cytokine, chemokine, and adhesion molecule expression, immune cell infiltration, myocardial injury, and contractile dysfunction (Erikson et al, 2017 ).…”
Section: Effects Of Modulation Of Jnk Activitymentioning
confidence: 99%
“…TRAF3IP2 (TRAF3 interacting protein 2; previously known as CIKS or Act1) is an oxidative stress-responsive cytoplasmic adapter molecule that is an upstream regulator of both IκB kinase (IKK) and JNK. Ischemia/reperfusion up-regulates TRAF3IP2 expression in the heart, and its gene deletion, in a conditional cardiomyocyte-specific manner, significantly attenuates ischemia/reperfusion-induced oxidative stress, IKK/NF-κB and JNK/AP-1 activation, inflammatory cytokine, chemokine, and adhesion molecule expression, immune cell infiltration, myocardial injury, and contractile dysfunction (Erikson et al, 2017 ).…”
Section: Effects Of Modulation Of Jnk Activitymentioning
confidence: 99%
“…Blocking GABA-A receptors increased this marker of myocardial injury and administration of bicuculline prior to SD attenuated the protective effects of SD. In this regard, Erikson et al (2017) demonstrated a considerable rise in LDH levels following myocardial IR, however these levels were lower as compared to chronic sleep deprivation (Periasamy et al 2015;Erikson et al 2017). In the current study, the myocardial hemodynamic parameters were studied to reflect cardiac functions.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the protective effect of ALDH2 is due to inhibition of JNK/AP-1 pathway. In the heart, both JNK and AP-1 are key regulators of myocardial remodeling [11,29]. In addition, hypertension-induced cardiac dysfunction is associated with increased AP-1 activity [5].…”
Section: Discussionmentioning
confidence: 99%